Poverty and Shared Prosperity in Brazil's Metropolitan Regions : Taking Stock and Identifying Priorities - World Bank Group (Washington, DC, 2015)
In the 20th Century, Brazil rapidly urbanized and is now not only an urban nation but a metropolitan one. Brazils sprawling regioes metropolitanas (metropolitan regions, or RMs, which are municipal clusters) are now home to almost 50 million people and much of the countrys economic vitality. The RM spatial level and its supporting governmental institutions have thus become critical to Brazils future development. While challenges remain for tackling deprivation in rural areas, poverty in Brazil is now predominantly urban. More than six in 10 Brazilians in extreme poverty were living in urban settings as of 2012. Of these, over a fourth was concentrated in the 10 largest RMs.